2009
DOI: 10.1186/1467-4866-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of 3'-(p-Aminophenyl) fluorescein for determining the formation of highly reactive oxygen species in particle suspensions

Abstract: BackgroundGiven the importance of highly reactive oxygen species (hROS) as reactants in a wide range of biological, photochemical, and environmental systems there is an interest in detection and quantification of these species. The extreme reactivity of the hROS, which includes hydroxyl radicals, presents an analytical challenge. 3'-(p-Aminophenyl) fluorescein (APF) is a relatively new probe used for measuring hROS. Here, we further evaluate the use of APF as a method for the detection of hydroxyl radicals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 47 publications
1
34
0
1
Order By: Relevance
“…Hence, adenine degradation in pyrite slurries is an indirect probe recording the formation of hydroxyl radicals. The direct determination of hydroxyl radicals in pyrite slurries using electron spin resonance spectroscopy (ESR) or fluorogenic probes (Cohn et al, , 2008(Cohn et al, , 2009) has been demonstrated, but these techniques do not lend themselves for experiments designed to provide kinetic data over a range of solution conditions. The ESR method requires access to an X-band ESR spectrometer and for each data point several controls have to be measured in order to demonstrate that the signal is derived from hydroxyl radical and not ferric iron.…”
Section: Adenine Degradation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, adenine degradation in pyrite slurries is an indirect probe recording the formation of hydroxyl radicals. The direct determination of hydroxyl radicals in pyrite slurries using electron spin resonance spectroscopy (ESR) or fluorogenic probes (Cohn et al, , 2008(Cohn et al, , 2009) has been demonstrated, but these techniques do not lend themselves for experiments designed to provide kinetic data over a range of solution conditions. The ESR method requires access to an X-band ESR spectrometer and for each data point several controls have to be measured in order to demonstrate that the signal is derived from hydroxyl radical and not ferric iron.…”
Section: Adenine Degradation Experimentsmentioning
confidence: 99%
“…Fluorogenic probes, such as 3 0 -(p-aminophenyl) fluorescein (APF), are molecules that will react specifically with hydroxyl radical and yield fluorescent daughter molecules. APF and other probes have been used by our group to compare hydroxyl formation among various materials using a protocol that requires the use of a phosphate buffer (Cohn et al, 2008(Cohn et al, , 2009. The use of the buffer prevents studying hydroxyl formation over a range of pH conditions.…”
Section: Adenine Degradation Experimentsmentioning
confidence: 99%
“…The experiments followed a previously published protocol for the determination of hydroxyl radical in mineral slurries (Cohn et al 2009). Natural pyrite from Huanzala, Peru, was purchased from Wards, crushed in an agate mill, sieved to less than 38 lm and stored under anoxic conditions until use.…”
Section: Fluorescence Assay Proceduresmentioning
confidence: 99%
“…OH and H 2 O 2 was determined using the protocol developed by Cohn et al (2009) (Cohn et al, 2009). The protocol is based on the conversion of non-fluorescent 3 '-(p-Aminophenyl) fluorescein (APF) to fluorescein, which is strongly fluorescent.…”
Section: Methodsmentioning
confidence: 99%
“…After 26 hours of mixing, the tubes were removed from the orbital shaker, filtered over Teflon micro-membrane filters with a pore size of 0.22 μm, and the fluorescence was measured on a Turner Design instrument, equipped with 490 (excitation) and 520 (emission) filters. A calibration curve made by diluting a 1 mM H 2 O 2 stock solution and reacting it with APF and HRP (Cohn et al, 2009). The fluorescence values recorded for the mineral slurries was converted to H 2 O 2 equivalents and expressed as nM/m 2 .…”
Section: Methodsmentioning
confidence: 99%